Polyploidy among salmonid aldehyde dehydrogenase genes and proteins. (25th April 2019) - Holmes, Roger S.
Abstract: Bioinformatic analyses of salmon ( Salmo salar ) ALDH amino acid sequences supported the presence of at least 30 ALDH genes, which is more than for any other higher vertebrate and is greater than the 19 human ALDH genes currently reported. These included 8 polyploid ALDH genes and proteins: ALDH1A2 (chromosomes 11 and 26); ALDH1L2 (chromosomes 7 and 17); ALDH2, encoding mitochondrial ALDH2 (chromosomes 2 and 5); ALDH3A2 (chromosomes 4, 9 and 20), for which evidence for 5 genes was obtained; ALDH3B1 (chromosomes 3, 6 and 24); ALDH4A1 (chromosomes 12 and 22); ALDH6A1 (chromosomes 1, 6 and 15); and ALDH18A1 (chromosomes 19 and 28). In contrast, 7 salmon ALDH gene families ( ALDH1A1, ALDH1A3, ALDH5, ALDH7, ALDH8, ALDH9 and ALDH16 ) possessed only one gene family member. Phylogenetic studies of salmon and rainbow trout ALDH3A2 genes and proteins suggested that salmonid gene tetraploidy has occurred in at least 2 distinct stages of ALDH3A2 gene evolution. Highlights: Vertebrate ALDHs metabolise many biological aldehydes in the body. Atlantic salmon ( Salmo salar ) ALDH genes encode at least 30 ALDH enzymes. This is much greater than the 19 human ALDHs currently reported. 8 polyploid salmon ALDH genes were observed, including ALDH1A2, ALDH2 and ALDH3A2 .